Stratified teaching module based on cognitive apprenticeship models in Chinese high school students’ mathematics performance, problem-solving ability and learning motivation - Wang, Ruimei (2024)
Conventional teaching methods have shown an inability to adapt to the distinct learning preferences of students. To address these issues, stratified teaching framed by the Cognitive Apprenticeship Model (CAM) was developed in this study to improve the performance, problem-solving ability, and learning motivation in mathematics for 9th-grade students. This innovative pedagogical approach was created by applying the ADDIE methodology for instructional design and incorporating information technology. For the empirical portion of this research, a quasi-experimental design was implemented in a high school in China. A total of 150 students were randomly allocated into three groups, with each group consisting of 50 students. One group was taught using the CAM approach (i.e., the teachers employed modeling, coaching, scaffolding, fading, articulation, and reflection techniques). Another group was exposed to the Stratified Cognitive Apprenticeship Model Teaching Module (SCTM), while the control group was taught using conventional instruction (CI), which mainly involved teacher lectures, student note-taking, and homework completion. The effects of the different teaching techniques were evaluated using pre-tests, post-tests, and delayed post-tests, which were compared to the MYP mathematics assessment standards and a questionnaire that measured motivation in studying mathematics. Analysis of covariance (ANCOVA) was performed using SPSS, and the findings indicated that the SCTM group exhibited superior performance in mathematical ability, problem-solving skills, and motivation for learning mathematics compared to the other groups. Therefore, this study supports using SCTM in high school mathematics, demonstrating its efficacy as a teaching technique. The findings of this study suggest that integrating SCTM with traditional teaching methods is a beneficial approach to improving students’ mathematics performance, problem-solving abilities, and learning motivation. The favorable results of the SCTM approach provide a strong foundation for its application in high school mathematics instruction and may influence future educational methodologies and policies.